HUBUNGAN ANTARA MINAT MEMBACA DENGAN KREATIVITAS VERBAL SISWA KELAS VI SEKOLAH DASAR - Jessica Arthin Novia; Arthur Huwae (Fakultas Psikologi Universitas Kristen Satya Wacana, 2023)
The problem of verbal creativity that occurs in grade VI elementary school students often causes them to be unable to show optimal learning achievement. Supported by low interest in reading, making students experience complex problems when following the learning process at school. This study aims to determine the relationship between interest in learning and verbal creativity in grade VI elementary school students. The method used is quantitative with a correlational design. The participants of this study were grade VI students of SD Kutowinangun 8 Salatiga in the 2022/2023 school year, totaling 49 students using saturated sampling technique. Measurements used reading interest scale and verbal creativity test. The results showed a strong significant positive relationship between interest in learning and verbal creativity of grade VI students of SD Kutowinangun 8 Salatiga (r = 0.941 and sig. = 0.000). The results concluded that interest in learning is one of the strong factors related to increasing students' verbal creativity.